2002
DOI: 10.1046/j.1525-1497.2002.11214.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of predictors of adherence to combination antiretroviral medication

Abstract: Nearly all patients' adherence levels were suboptimal, demonstrating the critical need for programs to assist patients with medication taking. Interventions that assess and treat substance abuse and incorporate adherence aids may be particularly helpful and warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
321
4
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(366 citation statements)
references
References 81 publications
24
321
4
10
Order By: Relevance
“…Entre esses obstáculos, o uso de álcool, que é um comportamento modificável, temse mostrado como um forte preditor de falhas na adesão e piora no desfecho clínico [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
“…Entre esses obstáculos, o uso de álcool, que é um comportamento modificável, temse mostrado como um forte preditor de falhas na adesão e piora no desfecho clínico [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
“…These findings echo those of Paterson et al (2000), who found that 63% of individuals with twicedaily dosing achieved 95% electronically monitored adherence to dosing and timing compared with 45% with thrice-daily dosing, P < .04. Golin et al (2002) studied a mostly male county hospital sample using a prospective design. They found a significant and moderate bivariate correlation between dose frequency per day and adherence (r = −0.25, P = 0.006).…”
Section: Hiv and Aidsmentioning
confidence: 99%
“…6 In pill count method, adherence is usually calculated by counting the remaining doses of medication and assuming that the remaining pills in excess of what is expected to represent missed doses. 7 In literature, very few studies are available depicting factors related to adherence in children, so study was undertaken with the aim to determine the prevalence of adherence to ART amongst HIV infected patients on ART and to determine the factors lead to adherence and non-adherence to ART.…”
Section: Introductionmentioning
confidence: 99%